2017
DOI: 10.1371/journal.pone.0175592
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of severe fever with thrombocytopenia syndrome virus in China: A systematic review and meta-analysis

Abstract: ObjectiveSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by a novel bunyavirus-SFTSV. The seroprevalence of anti-SFTSV antibodies including immunoglobulin G (IgG) and immunoglobulin M (IgM), specific to SFTSV in the general population has been investigated in various epidemiological studies with inconsistent results. Here, we clarify this discrepancy and reach a more comprehensive result by mean of a meta-analysis.MethodsAll relevant articles were searched in the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Furthermore, a recent study in South Korea reported that the seroprevalence of SFTS among patients visiting a tertiary hospital was 2.1%. The reasons for these discrepancies may be attributed, at least in part, to occupation, geographical location, and environmental conditions (10,21). However, it is more likely that the higher seroprevalence reported in China and South Korea might be because of the differences in the SFTSV antibody detection methods used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a recent study in South Korea reported that the seroprevalence of SFTS among patients visiting a tertiary hospital was 2.1%. The reasons for these discrepancies may be attributed, at least in part, to occupation, geographical location, and environmental conditions (10,21). However, it is more likely that the higher seroprevalence reported in China and South Korea might be because of the differences in the SFTSV antibody detection methods used.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is more likely that the higher seroprevalence reported in China and South Korea might be because of the differences in the SFTSV antibody detection methods used. Previous studies have used a double-antigen ELISA or an indirect ELISA to detect anti-SFTSV IgG antibodies (10,21). However, we used ELISA and IFA to screen the samples, and FRNA was used to confirm if the samples tested positive or negative for SFTSV antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of SFTSV infection has become an intractable public health issue in eastern and central China (Li et al, ). A previous study reported that the overall asymptomatic infection was 4.3%, and the hospital‐based investigation result showed that the incidence of SFTSV infection was evaluated as 8.4% in patients with a fever, thrombocytopenia and leukopenia in endemic areas of China (Huang et al, ; Li et al, ). Most SFTS cases were discovered and reported during the inpatient period after seeking treatment more than once.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the seasonal abundance of ticks 12 . Various epidemiological studies had investigated the prevalence of SFTSV in general populations and recognized that age was the critical risk factor or determinant for SFTSV morbidity and mortality 13 .…”
Section: Introductionmentioning
confidence: 99%